Comparison of the Value of Welfare Principles in National Law and Islamic Law - Manalu, Paris; Sugianto, Sugianto; Lala, Andi (Ann Publisher, 2023)
The welfare state stresses that everyone has the right to social services, not only means of managing welfare or social services. The polarization of the welfare state's primary aims is articulated, with the goal of establishing indications as a measuring instrument in determining whether the society is affluent or not. Talking about the concept of the rule of law, Islam as a perfect religion also has the concept of statehood. The approach method in this study is normative legal research. The type of research used in this study is descriptive research. The data sources obtained from the author are Primary legal material data sources and Secondary legal materials. The data collection method carried out in this study is a literature study. The data analysis method used in this study is qualitative method. The current status of social welfare shows that there are residents who have not received adequate public support for their fundamental necessities. As a result, there are still residents who face challenges in carrying out social tasks, preventing them from living a decent and dignified existence. Islam is not just a religion that contains a set of ritual doctrines, but it is a holistic worldview that is comprehensive and systematic. Islam as al-din covers all aspects of human life including aspects of statehood and law.